Pengembangan Aplikasi Mobile Tracer Study Menggunakan Platform Android - Ahmad Kamil Almasyhur; Herman Tolle; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tracer study system is a system that connects students who have graduated from educational institution with their friends who have graduated, which call as alumni. Alumni can give each other information about job vacancy to other alumni, the alumni can also provide information on current alumni work. Alumni can view information on alumni's work as well, then alumni can also provide educational information and view educational information that has been filled by the alumni themselves.There is no application that helps in the process of tracer study conducted in Faculty of Computer Science, Universitas Brawijaya (FILKOM UB), make the author the initiative in the process of developing mobile tracer study application using Android platform. This study uses prototyping SDLC (Software Development Lifecycle), which is written on the script of this thesis is the last prototype, or the final prototype. By using the firebase and Android platform, it is expected that the tracer study system can assist in the process of tracer study in FILKOM UB, with the result of the usability test is 80.625 (in range 0 - 100) included in the qualification is good enough, the result of functionality and compatibility generated by tracer study application capable of achieving perfect value on nougat and marsmallow operating system.